Sosialisasi Penanggulangan Judi Online dan Bahaya Narkoba Sebagai Perwujudan Masyarakat Penggerak Pancasila - Putri Dwi Utami (Jurnal Bina Desa, 2026)
The rise of online gambling and cases of drug abuse have given rise to unrest in society. In recent years, the trend of online gambling use and drug abuse has increased compared to previous years. The loss of inspiration for Pancasila values in national and state life is one of the factors influencing the widespread practice of online gambling and drug abuse. As a reflection of a dignified human being, there is an obligation, especially for students, to be able to dedicate themselves to society. Students, through service activities summarized in the Tri Dharma of Higher Education, have a big role in efforts to prevent online gambling and drugs as a concrete form of re-grounding the values of Pancasila. Students through their program of Kuliah Kerja Nyata or KKN realize that community empowerment is needed. Activities carried out to prevent online gambling and drug practices were held in Kebonagung Village, Bandongan District, Magelang Regency. The method used is in the form of socialization or counseling. This activity is to provide an understanding of the dangers of online gambling and drugs so that we can create a civilized society in accordance with the values of Pancasila.